Do biofilm formation and interactions with human cells explain the clinical success of Acinetobacter baumannii? - Anna de Breij; Lenie Dijkshoorn; Ellen Lagendijk; Joke van der Meer; Abraham Koster; Guido Bloemberg; Ron Wolterbeek; Peterhans van den Broek; Peter Nibbering (PLoS ONE, 2010)
BACKGROUND: The dramatic increase in antibiotic resistance and the recent manifestation in war trauma patients underscore the threat of Acinetobacter baumannii as a nosocomial pathogen. Despite numerous reports documenting its epidemicity, little is known about the pathogenicity of A. baumannii. The aim of this study was to obtain insight into the factors that might explain the clinical success of A. baumannii. METHODOLOGY/PRINCIPAL FINDINGS: We compared biofilm formation, adherence to and inflammatory cytokine induction by human cells for a large panel of well-described strains of A. baumannii and compared these features to that of other, clinically less relevant Acinetobacter species. Results revealed that biofilm formation and adherence to airway epithelial cells varied widely within the various species, but did not differ among the species. However, airway epithelial cells and cultured human macrophages produced significantly less inflammatory cytokines upon exposure to A. baumannii strains than to strains of A. junii, a species infrequently causing infection. CONCLUSION/SIGNIFICANCE: The induction of a weak inflammatory response may provide a clue to the persistence of A. baumannii in patients.